ORIENTATION AND THERMAL CYCLING EFFECTS ON THE CRITICAL CURRENTS OF HIGH-TC SUPERCONDUCTING COMPOSITES - Jenkins, R; Jones, H; Belenli, I; Yang, M; Goringe, M; Grovenor, C (1993)
Transport critical currents of short lengths of high Tc superconducting composite tapes have been measured as a function of magnetic field applied parallel to and perpendicular to the tape surface. Anisotropy factors have been calculated from the results on a number of samples, differing only in their final annealing temperatures, and show great similarity for samples whose critical current densities vary widely. We explain these results in terms of the different microstructures of the samples. We discuss n values and present some data on Ag magnetoresistance. Mechanisms leading to a degradation in Jc as a result of thermal cycling are described along with possible solutions. © 1993.